"Look at What They’ve Turned Us Into": Reading the Story of Lot’s Daughters with Trauma Theory and The Handmaid’s Tale - Cobb, Kirsi (Open theology, 2021)
The story of Lot’s daughters’ incest with their father in Genesis 19:30-38 has been variously understood as a myth, a trickster tale, and an androcentric phantasy. In this paper, I will use insights gained from trauma theory, as well as from the characters of Emily and Moira in the Hulu adaptation of Margaret Atwood’s The Handmaid’s Tale , to evaluate the daughters’ actions. Studying the characters in the final form of the text, the women undergo traumatic experiences as their father offers their bodies to be raped (Gen. 19:7-8) and they witness the destruction of their home (Gen. 19:24-25). Consequently, they engage in what could be described as a traumatic re-enactment with their father, where the roles of the perpetrator and the victim are reversed, and the continuation of the patriarchal line is simultaneously guaranteed. Read in conjunction with the fates of Emily and Moira, the daughters’ experience could be summarized in Emily’s observation, "Look at what they’ve turned us into." In the lives of all the women, the experience of cumulative and direct trauma influenced their decision making as well as the choices they had available. This leaves the audience in a moment of uncertainty, where evaluating the women’s actions becomes a complex, even an impossible prospect.